Methods and Techniques of Signal Processing in Physical Measurements - Hanus, Robert; Mazur, Damian; Kreischer, Christian (Lecture Notes in Electrical Engineering, 2019)
This book discusses selected issues of modern electrical metrology in the fields of sensor technology, signal processing and measurement systems, addressing theoretical problems and applications regarding measurements in electrical engineering, mechanics, telecommunications, medicine and geology, as well as in the aviation and transport industries. It presents selected papers from the XXII International Seminar of Metrology "Methods and Techniques of Signal Processing in Physical Measurements" (MSM2018) held in Rzeszów-Arłamów, Poland on September 17-20, 2018. The conference was organized by the Rzeszow University of Technology, Department of Metrology and Diagnostic Systems (Poland) and Lviv Polytechnic National University, Department of Information Measuring Technology (Ukraine). The book provides researchers and practitioners with insights into the state of the art in these areas, and also serves as a source of new ideas for further development and cooperation.